Aligning Microtomography Analysis with Traditional Anatomy for a 3D Understanding of the Host-Parasite Interface – Phoradendron spp. Case Study - Teixeira-Costa, Luíza; Ceccantini, Gregório C. T. (Frontiers in Plant Science, 2016)
The complex endophytic structure formed by parasitic plant species often represents a challenge in the study of the host-parasite interface. Even with the large amounts of anatomical slides, a three-dimensional comprehension of the structure may still be difficult to obtain. In the present study we applied the High Resolution X-ray Computed Tomography (HRXCT) analysis along with usual plant anatomy techniques in order to compare the infestation pattern of two mistletoe species of the genus Phoradendron. Additionally, we tested the use of contrasting solutions in order to improve the detection of the parasite’s endophytic tissue. To our knowledge, this is the first study to show the 3-dimensional structure of host-mistletoe interface by using HRXCT technique. Results showed that Phoradendron perrottetii growing on the host Tapirira guianensis forms small woody galls with a restricted endophytic system. The sinkers were short and eventually grouped creating a continuous interface with the host wood. On the other hand, the long sinkers of Phoradendron bathyoryctum penetrate deeply into the wood of Cedrela fissilis branching in all directions throughout the woody gall area, forming a spread-out infestation pattern. The results indicate that the HRXCT is indeed a powerful approach to understand the endophytic system of parasitic plants. The combination of 3-dimensional models of the infestation with anatomical analysis provided a broader understanding of the host-parasite connection. Unique anatomic features are reported for the sinkes of Phoradendron perrottetii, while the endophytic tissue of Phoradendron bathyoryctum conformed to general anatomy observed for other species of this genus. These differences are hypothesised to be related to the 3-dimensional structure of each endophytic system and the communication stablished with the host.